2015
DOI: 10.1155/2015/790209
|View full text |Cite
|
Sign up to set email alerts
|

Trigger Point Dry Needling and Proprioceptive Exercises for the Management of Chronic Ankle Instability: A Randomized Clinical Trial

Abstract: Objective. To compare the effects of combined trigger point dry needling (TrP-DN) and proprioceptive/strengthening exercises to proprioceptive/strengthening exercises on pain and function in ankle instability. Methods. Twenty-seven (44% female, mean age: 33 ± 3 years) individuals with unilateral ankle instability were randomly assigned to an experimental group who received proprioceptive/strengthening exercises combined with TrP-DN into the lateral peroneus muscle and a comparison group receiving the same prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 43 publications
(56 reference statements)
1
47
0
Order By: Relevance
“…After the full review process, 12 studies were selected for inclusion. 2,7,12,24,27,28,32,33,35,36,38,43 After contact with primary authors of included studies, 1 further study was identified for inclusion, 6 resulting in a total of 13 studies. The absolute degree of rater agreement for the first and second stages of the study selection was 86% and 93%, respectively.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the full review process, 12 studies were selected for inclusion. 2,7,12,24,27,28,32,33,35,36,38,43 After contact with primary authors of included studies, 1 further study was identified for inclusion, 6 resulting in a total of 13 studies. The absolute degree of rater agreement for the first and second stages of the study selection was 86% and 93%, respectively.…”
Section: Study Selectionmentioning
confidence: 99%
“…This systematic review focused on musculoskeletal pain and included 13 studies: 6 on neck pain (5 on mechanical neck pain 6,24,28,32,43 and 1 on chronic whiplash-associated disorder 38 ), 1 on postoperative shoulder pain, 2 1 on chronic lower back pain, 33 1 on total knee arthroplasty, 27 1 on chronic ankle instability, 35 2 on myofascial pain, 12,36 and 1 on fibromyalgia. 7 Inclusion and exclusion criteria varied greatly across the studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Study participants were seated on a treatment table during the hand dynamometry and no and scores on the Functional Ankle Ability Measure (FAAM) compared to proprioceptive exercises alone. 5 These participants received four needling interventions as compared to the single treatment provided in this study, so it is possible that multiple needling treatments are needed to gain enough improvement to be reflected in a functional assessment tool.…”
Section: Balancementioning
confidence: 99%
“…Previous investigators have shown abnormalities of the fibularis muscles in persons with CAI, including reduced reaction time, diminished postural control and corticomotor excitability, and the presence of myofascial trigger points (MTrPs). 5,6,7 MTrPs are areas of increased irritability in palpable taut bands of skeletal muscle tissue that are clinically associated with both local and referred pain, muscle dysfunction, and autonomic phenomena. [8][9][10] In addition to other intervention strategies, the use of dry needling as a treatment for MTrPs is gaining attention as investigations on its effectiveness emerge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation